Selective Regional Loss of Cortical Synapses Lacking Presynaptic Mitochondria in the 5xFAD Mouse Model - Seo, Na-young; Kim, Gyu Hyun; Noh, Jeong Eun; Shin, Ji Won; Lee, Chan Hee; Lee, Kea Joo (Frontiers in Neuroanatomy, 2021)
Synaptic loss in Alzheimer's disease (AD) is strongly correlated with cognitive impairment. Accumulating evidence indicates that amyloid pathology leads to synaptic degeneration and mitochondrial damage in AD. However, it remains unclear whether synapses and presynaptic mitochondria are differentially affected in various cortical regions of the AD brain at the ultrastructural level. Using serial block-face scanning electron microscopy, we assessed synaptic structures in the medial prefrontal cortex (mPFC) and primary visual cortex (V1) of the 5xFAD mouse model of AD. At 6 months of age, 5xFAD mice exhibited significantly elevated levels of amyloid deposition in layer 2/3 of the mPFC but not V1. Accordingly, three-dimensional reconstruction of synaptic connectivity revealed a significant reduction in excitatory synaptic density in layer 2 of the mPFC, but not V1, of male transgenic mice. Notably, the density of synapses lacking presynaptic mitochondria was selectively decreased in the mPFC of 5xFAD mice, with no change in the density of mitochondria-containing synapses. Further classification of spines into shape categories confirmed a preferential loss of thin spines whose presynaptic boutons were largely devoid of mitochondria in the 5xFAD mPFC. Furthermore, the number of mitochondria per bouton in spared mitochondria-containing boutons was reduced in the mPFC, but not V1, of 5xFAD mice. Collectively, these results highlight region-specific vulnerability of cortical synapses to amyloid deposition and suggest that the presence of presynaptic mitochondria may affect synaptic degeneration in AD.